H19-DMR allele-specific methylation analysis reveals epigenetic heterogeneity of CTCF binding site 6 but not of site 5 in head-and-neck carcinomas: A pilot case-control analysis - Esteves, LID; Cervigne, N. D.; Javaroni, A. D.; Magrin, J.; Kowalski, L. P.; Rainho, C. A.; Rogatto, Silvia Regina [UNESP] (Professor D A Spandidos, 2006)
Aberrant methylation of seven potential binding sites of the CTCF factor in the differentially methylated region upstream of the H19 gene (H19-DMR) has been suggested as critical for the regulation of IGF2 and H19 imprinted genes. In this study, we analyzed the allele-specific methylation pattern of CTCF binding sites 5 and 6 using methylationsensitive restriction enzyme PCR followed by RFLP analysis in matched tumoral and lymphocyte DNA from head-and-neck squamous cell carcinoma (HNSCC) patients, as well as in lymphocyte DNA from control individuals who were cancer-free. The monoallelic methylation pattern was maintained in CTCF binding site 5 in 22 heterozygous out of 91 samples analyzed. Nevertheless, a biallelic methylation pattern was detected in CTCF binding site 6 in a subgroup of HNSCC patients as a somatic acquired feature of tumor cells. An atypical biallelic methylation was also observed in both tumor and lymphocyte DNA from two patients, and at a high frequency in the control group (29 out of 64 informative controls). Additionally, we found that the C/T transition detected by HhaI RFLP suppressed one dinucleotide CpG in critical CTCF binding site 6, of a mutation showing polymorphic frequencies. Although a heterogeneous methylation pattern was observed after DNA sequencing modified by sodium bisulfite, the biallelic methylation pattern was confirmed in 9 out of 10 HNSCCs. These findings are likely to be relevant in the epigenetic regulation of the DMR, especially in pathological conditions in which the imprinting of IGF2 and H19 genes is disrupted.
Keywords: differentially methylated region; genomic imprinting; head-and-neck carcinomas; polymorphism; H19 gene